Insights from microRNAs into the pathophysiology of coronary and multiterritorial atherosclerosis. (25th November 2020) - Silva, T.P.D; Costa, M.C; Gabriel, A.F; Selas, M; Silva, F; Enguita, F.J; Napoleao, P; Goncalves, A; Ferreira, V; Bras, P; Castelo, A; Reis, J; et al.
Abstract: Introduction: The mechanisms underlying the different phenotypic presentations of atherosclerosis are still poorly understood. MicroRNAs regulate genetic expression at the post-transcriptional level and each has specific biological functions. MicroRNAs could therefore be useful for understanding the epigenetic drivers for development of isolated coronary atherosclerosis and more extensive disease (coronary and extra-coronary). We evaluated if the expression profile of circulating microRNAs was associated with coronary and multiterritorial atherosclerosis. Methods: We prospectively recruited three groups of age- and sex-matched participants, with: 1) no coronary atherosclerosis (calcium score=0, no soft plaques in coronary angioCT scan), neither carotid or inferior limbs atherosclerosis (controls); 2) isolated obstructive coronary artery disease (CAD) (≥50% for the left main, ≥70% for other epicardial vessels) (isolated CAD group); 3) obstructive disease of the coronary, inferior limbs and carotid arterial beds (multi-territorial disease group). Obstructive atherosclerosis of carotid and inferior limbs arteries (≥50% stenosis by Doppler or angioCT imaging) was assessed in all participants. Acute atherosclerotic events or coronary revascularization within 12 months, heart failure, infections, malignancy and severe renal dysfunction were exclusion criteria. Six microRNAs with diverse mechanisms of action were selected (mir-21, miR-27b, miR-29a, miR-126, miR-146, miR-218) and measurements of their circulating levels were performed in a blinded fashion, using RT-PCR SYBR Green. Results: Twenty four patients were included, including 8 patients in each group. Mean age was 61±9 years, and 83% were male. In patients with atherosclerosis, classical cardiovascular risk factors were globally more prevalent. The expression of miR-146 and miR-218, both of which regulate endothelial function, was significantly decreased in the isolated CAD group compared to controls (Figure; data are expressed as median [IQR]). There was a further decrease in the expression of both microRNAs in patients with multiterritorial atherosclerosis compared to patients with isolated CAD. The expression of other microRNAs did not differ. Smoking was associated with the presence of isolated CAD and multiterritorial atherosclerosis (14% vs 30% vs 56% of smokers across groups, p=0.002), and with a decreased expression of miR-218 (1.6 [0.02–83] fold vs 0.1 [0.001–0.7] fold, p=0.023). Conclusions: The expression of the endothelial regulators miR-146 and miR-218 was decreased in patients with isolated CAD compared to controls, and even more hampered in patients with multiterritorial atherosclerosis. Higher degrees of endothelial dysfunction may therefore contribute to a more diffuse atherosclerotic presentation through miR-146 and miR-218. Atherogenesis related to smoking may be partially mediated by miR-218. Funding Acknowledgement: Type of funding source: None